Effectiveness of Emergency Department Treatment of Pediatric Headache and Relation to Rebound Headache. Issue 12 (December 2020) - Sheridan, David C.; Dhatt, Saroop; Narayan, Kamil; Lin, Amber; Fu, Rongwei; Meckler, Garth D.
Abstract : Objective: This study aimed to assess the association between the degree of headache relief obtained in the pediatric emergency department (PED) with abortive treatment and unscheduled return visits to the PED for a recurrent or persistent headache within 72 hours. Methods: This was a retrospective observational study with 369 patients, all younger than 18 years, who presented to the PED with a primary complaint of either a headache or migraine. Patient and visit details were collected from the medical chart, along with presenting and discharge pain score. Percent pain reduction at discharge was determined through the following calculation: (Presenting Pain Score − Discharge Pain Score)/Presenting Pain Score. Associations were assessed using multivariable logistic regression. Results: No significant association was found between the percent pain reduction and return to the PED ( P = 0.49). Mean presenting pain score at the index visit was statistically higher for those who ended up returning to the PED versus those who did not (8.1 vs 7.4; P = 0.02). A trend toward increase in return visits was seen among patients who had a headache duration greater than 3 days (odds ratio, 1.99) and patients who experienced less than 50% pain reduction in the PED (odds ratio, 1.77). Conclusions: Complete resolution in the PED may not be necessary, given the lack of association between the degree of pain relief and revisit rates. Perhaps, the goal should be to achieve at least 50% pain reduction before discharge.